Socialization of Balanced Nutrition to Prevent Poor Nutrition in Toddlers at The Clinic of Self-Work Practices of The Rugun Midwife - Irwanto, Reno; Novia, Reni; Siregar, Wilda Wahyuni; Turnip, Meria; Ginting, Luci Riani (JURNAL PENGMAS KESTRA (JPK), 2023)
Malnutrition is a nutritional problem that is still quite a lot in Indonesia and still really needs to be addressed so it doesn't have negative impacts that are detrimental to both the toddlers themselves or their families and the country. The prevalence of malnutrition in Indonesia is still high and needs to be addressed and prevented so that the number does not increase. One of the factors that can cause a toddler to be malnourished is the mother's lack of knowledge regarding well balanced nutrition to give to toddlers. Therefore, in this service, balanced nutrition socialization is carried out for mothers of toddlers in an effort to prevent malnutrition in toddlers. This community service activity was carried out at the Rugun Midwife Independent Work Practice Clinic on May 10-16 2023. This community service activity was carried out in the form of socialization and was carried out in several stages, namely planning, education and final evaluation. The results of this activity show that mothers under five are very enthusiastic in participating in activities and listening to what is conveyed by the speakers. This is also shown by the results of the pre-test and post-test which show that the mother's knowledge after being given socialization increases in a better direction. It is necessary to carry out further analysis related to changes in attitudes and behavior of mothers under five in an effort to prevent malnutrition in toddlers at the Rugun Midwife Independent Work Practice Clinic.